Mechanical Tension Controls Granulation Tissue Contractile Activity and Myofibroblast Differentiation - Hinz, Boris (American Society for Investigative Pathology, 2001)
We have examined the role of mechanical tension in myofibroblast differentiation using two in vivo rat models. In the first model, granulation tissue was subjected to an increase in mechanical tension by splinting a full-thickness wound with a plastic frame. Myofibroblast features, such as stress fiber formation, expression of ED-A fibronectin and α-smooth muscle actin (α-SMA) appeared earlier in splinted than in unsplinted wounds. Myofibroblast marker expression decreased in control wounds starting at 10 days after wounding as expected, but persisted in splinted wounds. In the second model, granuloma pouches were induced by subcutaneous croton oil injection; pouches were either left intact or released from tension by evacuation of the exudate at 14 days. The expression of myofibroblast markers was reduced after tension release in the following sequence: F-actin (2 days), α-SMA (3 days), and ED-A fibronectin (5 days); cell density was not affected. In both models, isometric contraction of tissue strips was measured after stimulation with smooth muscle agonists. Contractility correlated always with the level of α-SMA expression, being high when granulation tissue had been subjected to tension and low when it had been relaxed. Our results support the assumption that mechanical tension is crucial for myofibroblast modulation and for the maintenance of their contractile activity.